Effectiveness of different pharmacological or non-pharmacological interventions on preventing coughing during extubation: a protocol for a systematic review and network meta-analysis - Qian Li; Di Yang; Zhichao Gong; Yixuan Wu; Longjun Yang (BMJ Open)
Introduction Coughing during extubation can lead to several postoperative complications, including surgical site bleeding, intracranial hypertension and high intraocular pressure. Currently, various pharmacological and non-pharmacological interventions are employed in clinical practice to reduce coughing during extubation. However, it is unclear which of these interventions has the best preventive effect and the fewest adverse events. Therefore, we plan to conduct a systematic review and network meta-analysis to compare the effects of all interventions.Methods and analysis We will search MEDLINE, Embase, Web of Science, Cochrane Central Register of Controlled Trials, CNKI and Wanfang databases, as well as reference lists from previously published papers, from the date of their inception to April 2024. We will only include randomised controlled trials, regardless of publication in any language. The primary outcome is the incidence of cough during extubation, using the modified Minogue scales. The secondary outcomes are as follows: (1) the incidence of severe coughing (grade 4); (2) the incidence of other types of postoperative airway complications, such as laryngospasm, apnoea, hypoxaemia and sore throat, which will be evaluated within 24 hours after surgery; (3) the side effects related to the interventions, such as bradycardia (heart rate less than 60 beats per minute), hypotension or allergic reactions, which will be evaluated within 24 hours from the start of the drug to the postoperative period and (4) the time from the end of the surgery to the extubation of the endotracheal tube. The articles meeting the criteria will be independently evaluated by two researchers based on the established screening criteria. The data will then be extracted. Bias will be assessed for all included studies using the Cochrane Risk of Bias Risk Assessment Tool Version 2. We will use the Netmeta package of the R software with a random-effects model to make direct and indirect comparisons through the frequency framework. We will assess the quality of evidence using Confidence in Network Meta-Analysis.Ethics and dissemination Ethical approval is not required for this protocol, as we will only pool published data. We plan to submit our manuscript for publication in a peer-reviewed academic journal.PROSPERO registration number CRD42023401609.